Determining Value Co-Creation Behaviour toward Customer Loyalty and Customer Retention on the SRC’s Business Platformorm - Baehaqi, Muhammad; Cahyono, Ragil Setya; Riptiono, Sulis (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 17 Nomor 1 Tahun 2023DO - 10.24843/MATRIK:JMBK.2023.v17.i01.p04, 2023)
Customer retention is the maintenance of long-term customer-company relationships through customer satisfaction thereby creating loyalty. Value co-creation is proven to have a significant role in creating customer loyalty, so that customer loyalty becomes actual retention for the company. The role of shared value creation should be considered in customer relationship mechanisms. This study aims to produce an analysis of the role of value co-creation behavior on customer retention. This focus is novelty in research, because no confirmation was found in previous studies that produced a relationship between the two. Customer loyalty is the variable that mediates the relationship between value creation behavior and customer retention. This research produces findings regarding the positive influence of customer involvement through value co-creation behavior on retention as a long-term customer relationship mechanism with the company.   Keywords: value coreation behaviour; customer loyalty; customer retention